Archives as Agents of Change in Digital Transformation: Archives as a Catalyst For Bureaucratic Reform in The Era of Digital Government - Yolanda Maria Osok; Suparno Suparno; Tri Lestari Hadiati (International Forum of Researchers and Lecturers, 2026)
This research aims to analyse the role of archives as agents of change in the digital transformation of archives and as catalysts for bureaucratic reform in the era of digital government at the Sorong City Regional Secretariat. The research used a mixed-methods approach, combining a quantitative survey of 30 respondents with in-depth interviews with five key informants, and analysed the data using correlation statistics and thematic analysis. The study's results show that the digital transformation of archives is closely linked to bureaucratic reform and digital governance, and qualitative findings confirm that digitisation improves administrative efficiency, data integration, and organisational accountability. The research highlights the importance of strengthening technological infrastructure, integrating information systems, and improving the competence of the apparatus as prerequisites for the success of the digital transformation of archives. This study has limitations in its scope, involving only one local government agency and a relatively small number of respondents. Therefore, further research is recommended to broaden the scope, incorporate public service quality variables, and use a longitudinal design to examine the long-term impact of archive digitisation on the performance of bureaucratic reform and digital governance more comprehensively. These findings also provide practical contributions for local governments in designing integrated, sustainable electronic archive management policies that support effective, transparent, and responsive public services to meet the needs of modern society in the future, as well as strengthening data-driven governance.